Learning from physical and virtual investigation: A meta-analysis of conceptual knowledge acquisition - Muilwijk, Sifra E.; Lazonder, Ard W. (Frontiers in Education, 2023)
Should students investigate with tangible objects and apparatus or are digitally simulated materials and equipment an adequate or perhaps even preferred alternative? This question remains unanswered because empirical evidence is inconclusive and previous reviews are descriptive and synthesize a limited number of studies with small samples. This meta-analysis, therefore, assessed the relative effectiveness of physical versus virtual investigation in terms of conceptual knowledge acquisition and examined whether and how the aggregate effect size was moderated by substantive and methodological study features. Following a systematic search of Web of Science and ERIC for the period 2000–2021, 35 studies comparing physical and virtual investigations were selected for inclusion. Hedges’ g effect sizes for conceptual knowledge acquisition were computed and analyzed using a random effects model. The results showed no overall advantage of either mode of investigation (g = −0.14, 95% CI [−0.33, 0.06]). However, moderator analysis indicated that virtual investigation is more effective for adults compared with adolescents and children, and when touching objects or equipment does not provide relevant sensory information about the concept under study. These results imply that STEM teachers can decide for themselves whether to opt for physical or virtual investigation except when teaching adult students or when touch sensory feedback is substantively irrelevant; in those cases, virtual investigation is preferable.